2018
DOI: 10.1002/jcb.27862
|View full text |Cite
|
Sign up to set email alerts
|

High‐density lipoprotein functionality and breast cancer: A potential therapeutic target

Abstract: Breast cancer is a major cause of death globally, and particularly in developed countries. Breast cancer is influenced by cholesterol membrane content, by affecting the signaling pathways modulating cell growth, adherence, and migration. Furthermore, steroid hormones are derived from cholesterol and these play a key role in the pathogenesis of breast cancer. Although most findings have reported an inverse association between serum high‐density lipoprotein (HDL)‐cholesterol level and the risk of breast cancer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 107 publications
(344 reference statements)
1
18
0
Order By: Relevance
“…These findings are consistent with studies that have shown increased SR-B1 expression in cancer cells, suggesting that during carcinogenesis, tumor cells use HDL to meet their needs for cholesterol [171]. It has been shown that SR-B1 expression is directly proportional to tumor aggressiveness and that tumor progression is reduced by a decrease in SR-B1 activity and expression [169,172]. Diminished HDL-C levels, which are characteristic of cancer, are accompanied by increased expression of SR-B1 [146].…”
Section: Hdl and Cholesterol Trafficking In Crcsupporting
confidence: 90%
“…These findings are consistent with studies that have shown increased SR-B1 expression in cancer cells, suggesting that during carcinogenesis, tumor cells use HDL to meet their needs for cholesterol [171]. It has been shown that SR-B1 expression is directly proportional to tumor aggressiveness and that tumor progression is reduced by a decrease in SR-B1 activity and expression [169,172]. Diminished HDL-C levels, which are characteristic of cancer, are accompanied by increased expression of SR-B1 [146].…”
Section: Hdl and Cholesterol Trafficking In Crcsupporting
confidence: 90%
“…Beyond serum HDL‐cholesterol and apoA1 levels, the composition and functionality of HDL particles has been implicated in the pathophysiology of chronic diseases, including cancer (Andersen, 2018; Andersen and Fernandez, 2013; Navab et al, 2009; Samadi et al, 2019). Variability in HDL profiles may underlie studies that report conflicting associations between HDL‐cholesterol and chronic disease risk (Barter and Rye, 2017; Pirro et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in cholesterol pathways such as de novo synthesis, cell internalization, and cholesterol transport mediated by plasmatic lipoproteins could regulate several mechanisms in the development of BC [31]. Very low density lipoproteins (VLDL) and LDL could be critical in several mechanisms of tumor progression [32].…”
Section: Role Of Serum Lipoproteinsmentioning
confidence: 99%